2018
DOI: 10.1053/j.gastro.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intestinal Microbiota Lead to Production of Interleukin 17 by Intrahepatic γδ T-Cell Receptor–Positive Cells and Pathogenesis of Cholestatic Liver Disease

Abstract: In Mdr2 mice, we found development of liver fibrosis and inflammation to require hepatic activation of γδ TCR cells and production of IL17 mediated by exposure to L gasseri. This pathway appears to contribute to development of cholestatic liver disease in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 50 publications
3
87
0
Order By: Relevance
“…IL-17A has profibrogenic functions through recruitment of proinflammatory monocytes, increased production of TGF-, and enhanced TGF- responses in HSCs (6)(7)(8)(9)(10). IL-22 is hepatoprotective during acute liver injury (11,12), but its function during chronic injury is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…IL-17A has profibrogenic functions through recruitment of proinflammatory monocytes, increased production of TGF-, and enhanced TGF- responses in HSCs (6)(7)(8)(9)(10). IL-22 is hepatoprotective during acute liver injury (11,12), but its function during chronic injury is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the involvement of Th17 cells and IL-17 has been reported in several animal models of NAFLD progressing to NASH (27-31). Tedesco et al (32) reported the devel-opment of liver fibrosis and inflammation requires hepatic activation of γδ TCR + cells and production of IL-17 mediated by exposure to Lactobacillus gasseri that is translocated to the liver due to increased intestinal permeability in Mdr2 −/− mice. It is thought that dysbiosis, which is one of the pathogeneses of NASH, causes the proliferation and activation of Th17 cells and induces the overproduction of IL-17, thereby leading to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of intestinal Lactobacillus was found in mice with liver injury induced by acute concanavalin A (Con A) treatment, which can prevent further liver inflammation through activation of IL-22 production [38]. Furthermore, conflicting evidence supporting either a detrimental [39,40] or beneficial [14,41] effect of GM can be found for the liver injury in the ATP-binding cassette, sub-family B (MDR/TAP), member 4 (Mdr2) knockout (Mdr2 -/-) mice.…”
Section: Gut Dysbiosis Can Be An Adaptive Response To Liver Injurymentioning
confidence: 99%